Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/app.35613
|View full text |Cite
|
Sign up to set email alerts
|

A polymer–drug conjugate for doxorubicin: Synthesis and biological evaluation of pluronic F127‐doxorubicin amide conjugates

Abstract: Higher molecular weight of the polymer carrier is the basis for enhanced accumulation of the pro-drug in a solid tumor tissue due to a tumor-related phenomenon described as the enhanced permeability and retention (EPR) effect. The anticancer drug doxorubicin was covalently bound to F127 through amide group susceptible to lysosomal hydrolysis. The in vitro and in vivo properties of F127-DOX amide conjugates were studied. F127-DOX amide conjugates (M w : 13,400) were stable in neutral circumstance and showed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In vitro cytotoxicity of these prodrugs for murine leukemia cell lines P388/O and L1210/O was studied (Table 10). The cytotoxicitiy of prodrugs 1−3, having an ester linkage between Ptx and PEG, were very close to the cytotoxicity of 60 (c) Doxpoly(lactic-co-glycolic acid) (Dox-PLGA), 251 (d) folic acid-polyethylene glycol-Dox (Fol-PEG-Dox), 214 (e) polyethylene glycol-block-peptide-Dox (PEG-b-peptide-Dox), 256 (f) folic acid-polyethylene glycol-block-polycaprolactone-Dox (Fol-PEG-b-PCL-Dox), 11 (g) polyethylene glycol-Dox (PEG-Dox), 12 (h) pluronic F127-Dox (F127-Dox), 47 (i) Dox-aconitic acid linker-polyethylene glycol (Dox-CA-PEG), 45 (j) Dox-succinic acid linkerpolyethylene glycol (Dox-SA-PEG). free Ptx, which implies the release of Ptx by hydrolysis of the ester bond.…”
Section: End-functionalization Of Polymers With Drugsmentioning
confidence: 99%
“…In vitro cytotoxicity of these prodrugs for murine leukemia cell lines P388/O and L1210/O was studied (Table 10). The cytotoxicitiy of prodrugs 1−3, having an ester linkage between Ptx and PEG, were very close to the cytotoxicity of 60 (c) Doxpoly(lactic-co-glycolic acid) (Dox-PLGA), 251 (d) folic acid-polyethylene glycol-Dox (Fol-PEG-Dox), 214 (e) polyethylene glycol-block-peptide-Dox (PEG-b-peptide-Dox), 256 (f) folic acid-polyethylene glycol-block-polycaprolactone-Dox (Fol-PEG-b-PCL-Dox), 11 (g) polyethylene glycol-Dox (PEG-Dox), 12 (h) pluronic F127-Dox (F127-Dox), 47 (i) Dox-aconitic acid linker-polyethylene glycol (Dox-CA-PEG), 45 (j) Dox-succinic acid linkerpolyethylene glycol (Dox-SA-PEG). free Ptx, which implies the release of Ptx by hydrolysis of the ester bond.…”
Section: End-functionalization Of Polymers With Drugsmentioning
confidence: 99%
“…Unfortunately, most anticancer drugs show systemic side effects due to nonspecific uptake by the healthy noncancerous tissue. Side effects associated with chemotherapy limit the dose or cumulative doses that can be administered to the patients, which can lead to relapse of tumors as well as development of drug resistance [17]. In order to reduce the harm to normal cells and effectively kill the cancer cells, it is crucial to target the release of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unique polymorphism character of Pluronic and biocompatibility, they are used as drug carriers. Drug delivery systems for doxorubicin based on the Pluronic F127 have been prepared for target specific drug delivery [24,25], bio-imaging [26] and for activity against multidrug-resistant cells [27]. Similarly, drug delivery systems comprising of P123 have also been used for targetspecific drug delivery [28] and nano-sized drug delivery systems [29] of doxorubicin.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on fluorescence quenching of DOX by the nucleotide, adenosine-5′-monophosphate revealed that DOX exists in two conformations having a difference in hydrogen bonding [30]. The concentration of DOX used in different Pluronic/ DOX systems ranges from 10 −3 to 10 −5 M [23,24,31]. However, DOX self-associates to form dimers in aqueous solutions at higher concentrations, and in the nanosecond timescales the dimers are reportedly non-fluorescent and have no significant pharmaceutical importance [1].…”
Section: Introductionmentioning
confidence: 99%